Insights into uranium enrichment of indigenous electroactive Shewanella putrefaciens - Yang, Guolin; Wei, Ling; Liu, Liang; Mu, Bo; Chen, Tao (Frontiers in Microbiology, 2026)
Bioremediation of uranium-contaminated environments using native bacteria shows great promise. While Shewanella putrefaciens (S. putrefaciens) is a known uranium reducing bacterium, the mechanisms and adaptability of indigenous strains from uranium mine tailings remain unexplored. This study isolated a dominant indigenous strain of S. putrefaciens and employed a combined genomic and spectroscopic approach to elucidate its unique uranium fixation mechanism. Microbial diversity analysis confirmed the dominance of Shewanella in the oligotrophic and radioactive tailings. Whole-genome sequencing revealed a significant enrichment of genes related to energy metabolism and stress resistance, providing a genetic basis for its survival and activity. Crucially, by combining advanced spectroscopic techniques with an MtrA gene knockout experiment, we deciphered the specific role of the Mtr pathway in extracellular electron transfer for uranium reduction. Remarkably, the isolated strain achieved a uranium removal efficiency of up to 93% under experimental conditions, demonstrating its high potential for uranium bioremediation. This work not only provides a robust indigenous candidate for bioremediation but also delivers novel mechanistic insights into the uranium transformation processes of indigenous Shewanella, advancing strategies for the application of tailored microbiomes in radioactive waste management.